The Implementation of Fun-Based Learning as a Deep Learning Approach Strategy in 21st Century Education: A Perspective Study of Social Studies Teachers in Bandung City - Syahida Karim; Muhamad Parhan (SAINTIS Publishing, 2025)
In the era of globalization and the Fourth Industrial Revolution, 21st-century education demands a transformation towards learner-centered approaches that are enjoyable, meaningful, and reflective. Fun-Based Learning (FBL) is a strategy that supports the implementation of deep learning, especially in Social Studies (IPS) education. This study aims to explore the perspectives of Social Studies teachers in Bandung City regarding the application of FBL as a strategy for deep learning. A descriptive qualitative method was employed involving 30 Social Studies teachers as respondents through questionnaires and in-depth interviews. The results indicate that most teachers have yet to fully understand that FBL can effectively support deep learning. However, those who have implemented FBL acknowledge that this approach enhances students’ emotional engagement, motivation, and deep understanding of Social Studies material. These findings align with constructivist and humanistic learning theories emphasizing active, enjoyable, and reflective learning experiences. In conclusion, FBL is a relevant and effective strategy to strengthen deep learning in Social Studies education today, but improved teacher understanding and training are needed for optimal implementation in accordance with the Merdeka Curriculum and 21st-century education demands.